Pengaruh Financial Literacy dan Financial Planning terhadap Financial Management dengan Financial Attitude sebagai Variabel Mediasi Pada Karyawan PT. Yih Quan Footwear Indonesia - Nikmatul Khasanah; C. Tri Widiastuti; Noni Setyorini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine and analyze the influence of financial literacy and financial planning on financial management with financial attitude as a mediating variable among production employees of PT. Yih Quan Footwear Indonesia. This research employs a quantitative approach. The population consists of production employees of PT. Yih Quan Footwear Indonesia located in the Batang Integrated Industrial Estate, with a total sample of 112 respondents. Data were collected through an online questionnaire distributed via Google Form. The data analysis technique includes the analysis of the structural model (Inner Model), measurement model (Outer Model), and hypothesis testing. Data processing was carried out using SmartPLS 4 software. The results indicate that financial literacy has no significant effect on financial management, while financial planning has a positive and significant effect on financial management. Furthermore, financial literacy positively and significantly influences financial attitude, whereas financial planning shows no significant effect on financial attitude. Financial attitude has a positive and significant impact on financial management and mediates the relationship between financial literacy and financial management. However, financial attitude does not fully mediate the relationship between financial planning and financial management. These findings highlight the importance of enhancing employees’ financial literacy and attitudes to enable more prudent, structured, and sustainable financial management.